Tree Diversity, Structure and Functional Trait Identity Promote Stand Biomass Along Elevational Gradients in Subtropical Forests of Southern China. Issue 10 (27th September 2022) - Wu, Anchi; Tang, Xuli; Li, Andi; Xiong, Xin; Liu, Juxiu; He, Xinhua; Zhang, Qianmei; Dong, Anqiang; Chen, Hongfeng
Abstract: Subtropical forests play an important role in regulating global carbon storage, a substantial portion of these forest carbon pools are stored in biomass stocks. Yet, we do not fully understand how tree diversity, stand structure and functional trait identity influence biomass stocks along elevational gradients. Here we used forest inventory data from nine 1‐ha plots across different elevational gradients in subtropical forests of southern China. We analyzed the effects of tree diversity, structure and functional trait identity on biomass along elevational gradients, and tested the complementarity effect, selection effect, mass‐ratio hypothesis and specie‐energy hypothesis. We found that multiple metrics of diversity and structural attributes significantly promoted biomass. Forest biomass was improved by traits with greater maximum height, larger seed mass (SM) and lower wood density (WD). Specifically, large‐diameter trees were the strongest independent predictor of biomass relative to other single variables. A significant increase in tree diversity, density and biomass was observed with increasing elevational gradients; additionally, trees dominated by traits related to greater maximum tree height, larger SM and lower WD also increased. Elevation indirectly increased biomass by increasing diversity and community‐weighted mean traits, but indirectly decreased it by reducing structural attributes. Our results support the complementarity effect, selection effect and mass‐ratio hypothesis simultaneously, but not the species‐energy hypothesis. The selection effect had greater effects on stand biomass than the complementarity effect and mass‐ratio hypothesis. Our findings suggest that developing natural tree diversity and structural complexity as well as dominant resource‐acquisitive species is beneficial to maintain and enhance carbon storage capacity in species‐rich subtropical forests along elevational gradients. Plain Language Summary: Understanding the effects of both abiotic and biotic factors on forest biomass is important for forecasting the consequences of global change and for effectively managing carbon storage. We used forest inventory data from nine 1‐ha plots across sites and across different elevational gradients in subtropical forests of southern China to quantify the effects of tree diversity, stand structure and functional trait identity on stand biomass, and tested the complementarity effect, selection effect, mass‐ratio hypothesis and specie‐energy hypothesis. We found that multiple metrics of diversity and structural attributes significantly promoted biomass. Forest biomass was also improved by traits with greater maximum height, larger seed mass (SM) and lower wood density (WD). Specifically, large‐diameter trees had the strongest positive association with biomass relative to other single variables. Tree diversity, density and biomass increased significantly with increasing elevational gradients. Trees related to greater maximum tree height, larger SM and lower WD increased along elevational distributions. Elevation indirectly increased biomass through increasing tree diversity and community‐weighted mean traits, but indirectly decreased it through reducing structural attributes. Our results highlight that the selection effect had a greater influence on ecosystem functioning than the complementarity effect and the mass‐ratio hypothesis. Note that the study did not support the species‐energy hypothesis. Our findings provide new insights into the mechanisms that regulate carbon storage along local‐scale elevational gradients in species‐rich subtropical forests. Key Points: Larger‐diameter trees were the strongest independent predictor of stand biomass relative to other single factors The selection effect had a greater influence on the biomass of subtropical forests than the complementarity effect and the mass‐ratio hypothesis Tree diversity, density, biomass and dominant trait identity increased along increasing elevational gradients, not supporting the species‐energy hypothesis